Geographical drivers and climate-linked dynamics of Lassa fever in Nigeria - David W. Redding (Nature Portfolio, 2021)
Lassa Fever is a rodent-borne viral haemorrhagic fever that is a public health problem in West Africa. Here, the authors develop a spatiotemporal model of the socioecological drivers of disease using surveillance data from Nigeria, and find evidence of climate sensitivity.